Penerapan Model Pembelajaran Kooperatif Tipe Jigsaw untuk Meningkatkan Penggunaan Bahasa Indonesia yang Benar dalam Menulis Paragraf pada Siswa Kelas II di SD GMIT Bonipoi 3456 Kota Kupang - Abraham, Rini Marselina; Djawa, Alex; Sampe, Markus (ARZUSIN, 2025)
The ability to write paragraphs in accordance with Indonesian language conventions remains a challenge for Grade II students at SD GMIT Bonipoi 3456, Kota Kupang, highlighting the need for an effective and engaging learning model to improve this skill. This study aims to examine the effectiveness of the Jigsaw type of cooperative learning model in enhancing students’ ability to write proper paragraphs. The research employed a Classroom Action Research (CAR) method conducted in two cycles and involved 27 Grade II students. A mixed-methods approach was used, combining qualitative and quantitative techniques, with data collected through observations of teacher and student activities, interviews, learning outcome tests, and documentation. The results showed that the implementation of the Jigsaw model significantly improved students’ paragraph writing skills, as indicated by an increase in the percentage of learning mastery from 51.85% in Cycle I to 96.29% in Cycle II, and an increase in the average score from 55 to 95. Additionally, improvements were observed in the learning activities of both teachers and students. These findings indicate that the Jigsaw model not only enhances writing ability but also promotes active participation and a more enjoyable learning environment. The practical implication of this study is that teachers can apply the Jigsaw model as an alternative instructional strategy to effectively develop writing skills in Indonesian language learning at the elementary school level.